Lymphatic malformation with acquired Horner syndrome in an infant. (11th January 2018) - Spors, Birgit; Seemann, Joerg; Homer, Natalie; Fay, Aaron
Abstract : An infant presented with right upper eyelid ptosis and was subsequently diagnosed with acquired Horner syndrome. Further evaluation revealed a right-sided cervicothoracic lymphatic malformation. At 13 weeks of age, the child underwent percutaneous intracystic sclerotherapy with a mixture of sodium tetradecyl sulphate and ethanol. Twenty-one weeks after initial treatment, ophthalmic examination showed complete resolution of the blepharoptosis and pupillary miosis. Percutaneous sclerotherapy not only effectively treated the space-occupying lymphatic malformation but also reversed the Horner syndrome that was presumably induced by neural tension (more likely) or compression.